Influence of Carbon Pulse Ion Beam on Titanium Alloy; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Beloglazova P. A. Polina Andreevna; Chernov I. P. Ivan Petrovich; Cherdantsev Yu. P. Yuriy Petrovich; Pushilina N. S. Natalia Sergeevna (Materials Science and Technologies, 2015)
Title screen